Health Benefits and Chemical Composition of Matcha Green Tea: A Review - Kochman, Joanna (Molecules, 2020)
Japanese matcha is a type of powdered green tea, grown in a traditional way. Shading of the plants during the growth period enhances the processes of synthesis and accumulation of biologically active compounds, including theanine, caffeine, chlorophyll and various types of catechins. Green tea contains four main catechins, i.e., (−)-epicatechin (EC), (−)-epicatechin-3-gallate (ECG), (−)-epigallocatechin (EGC) and (−)-epigallocatechin-3-gallate (EGCG), of which the latter is the most active and abundant and matcha is their best condensed source. Due to its unique chemical composition and prized flavour, which sets it apart from other tea beverages, it is considered the highest quality tea. Its health-promoting properties are attributed to the high content of antioxidant and anti-inflammatory substances. Studies confirming the high antioxidant potential of tea beverages claim that it originates from the considerable content of catechins, a type of phenolic compound with beneficial effects on human health. Due to its potential for preventing many diseases and supporting cognitive function, regular consumption of matcha may have a positive effect on both physical and mental health. The aim of this review was to compile the health benefits of matcha tea. It is the first such review to be undertaken, and presents its main bioactive compounds in a systematic manner.